ISOLASI DAN ANALISIS GEN YANG RESPONSIF TERHADAP CEKAMAN KEKERINGAN PADA TEBU - Wiwit Budi Widyasari; Bambang Sugiharto; Cahya Ismayadi; Kabul Wahjudi; Untung Murdiyatmo (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2004)
This study was aimed to isolate and identify a gene that was responsive to drought stress in sugar cane variety M442-51, a variety that is widely used in pastures or dry land. Under drought stress, M442-51 showed an enhance expression of several proteins. One of the protein, namely dip22, (drought inducible protein, with a molecular weight of 22KDa) was isolated and analyzed. Amino acid sequence of this protein showed some homology with several stressed related proteins (OsAsr 1 from Oryza sativa leaves, ZM Bss1 of Zea mays leaves, LeAsr 1, LeAsr 2 and LeAsr 3 of Lycopersicum lycopersicon leaves). The 343 bp of dip22-cDNA fragment was obtained using RT PCR from mRNA of sugar cane leaves that has been exposed to drought stress. The results indicated that the gene dip22 plays an important role as a regulatory protein that are usually nested within cytoplasmic matrix or in the nucleus.